LITERATURE REVIEW: PERAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM MENINGKATKAN CITRA POSITIF BANK SYARIAH DI MASYARAKAT - Aisah Citra Ayu; Intan Nur Fadillah; Robiatul Adawiyah; Anis Fadhilah Pramono (P3M Trisakti School of Insurance (TSI), 2023)
Corporate Social Responsibility (CSR) is one of the public relations strategies that can be used to create a positive image of the company in the eyes of stakeholders. Companies are expected to implement CSR programs, particularly in the Islamic banking sector. For companies in the field of Islamic banking, the implementation of CSR programs becomes increasingly important as it reflects the company's commitment to applying Islamic economic principles based on Islamic values. This research aims to gather and analyze articles related to the role of Corporate Social Responsibility (CSR) in enhancing the positive image of Islamic banks in society. The research method used is a literature review. The databases Google Scholar and Neliti.com were searched from 2016 to 2023 using keywords such as Corporate Social Responsibility (CSR) and Company Image / Brand Image. By employing the Literature Review method, the results obtained by the author show that Corporate Social Responsibility (CSR) plays a crucial role in improving the image of Islamic banking institutions in Indonesia. The implementation of CSR has a positive and significant impact on the public's perception of Islamic banking institutions and represents a long-term investment that ensures sustainable existence for Islamic banks in Indonesia in the future.